Wincenty Pol i ks. Karol Antoniewicz – wspólnota ducha i twórczości - Leszczyńska, Bożena (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Wincenty Pol and Fr. Karol Antoniewicz were born in the same – 1807 year. Pol admired Fr. Antoniewicz and other Polish Armenians for their work for the good of the homeland, for introducing the Polish language, Polish customs, and the Catholic faith. Just as Fr. Antoniewicz had, W. Pol participated in the November Uprising, as well as participated in the dramatic events of the Galician Slaughter of 1846 and the Kraków fire in 1850. At that time, they must have met in person, too. Both poets connected the love of their homeland’s nature with the beauty of Polish patriotism, and had the conviction that the community of faith and language were sources of the nation’s identity. Both published their first writings in Lwów. Their poetry served to invigorate hearts. Both frequently referred to the tradition of prayer. Their activity was suffused by a simplicity. Franciszek Wężyk wrote that Pol was a talented writer, who combined beautiful abilities with a gold heart: „His thoughts are as sparks from heaven, and the sound of words - music”. These words also fit beautifully to the figure of Fr. Antoniewicz, a poet who is also worth remembering. Both, thanks to their deep faith in God’s Providence, retained their dignity and serenity in the deep night of suffering.